The interplay between immunity and aging in Drosophila [version 1; referees: 2 approved] - Kathrin Garschall; Thomas Flatt (F1000Research, 2018)
Here, we provide a brief review of the mechanistic connections between immunity and aging—a fundamental biological relationship that remains poorly understood—by considering two intertwined questions: how does aging affect immunity, and how does immunity affect aging? On the one hand, aging contributes to the deterioration of immune function and predisposes the organism to infections (“immuno-senescence”). On the other hand, excessive activation of the immune system can accelerate degenerative processes, cause inflammation and immunopathology, and thus promote aging (“inflammaging”). Interestingly, several recent lines of evidence support the hypothesis that restrained or curbed immune activity at old age (that is, optimized age-dependent immune homeostasis) might actually improve realized immune function and thereby promote longevity. We focus mainly on insights from Drosophila, a powerful genetic model system in which both immunity and aging have been extensively studied, and conclude by outlining several unresolved questions in the field.